2019
DOI: 10.3390/en12061128
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Mechanisms of a Crosswind on the Thermo-Hydraulic Characteristics of a Large-Scale Air-Cooled Heat Exchanger

Abstract: For the large scale air-cooled heat exchanger of a natural draft dry cooling system (NDDCS) in power plants, its thermo-flow characteristics are basically dominated by crosswinds. Unfortunately however, the detailed mechanisms of the crosswind effects have yet to be fully uncovered. Therefore, in this research, the local flow and heat transfer performances of the cooling deltas, which are also termed as the fundamental cells of the large-scale air-cooled heat exchanger, are specifically investigated with full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…However, as a critical heat transfer element, the heat transfer characteristics and aerodynamic fields of cooling deltas are also a research focus. Kong et al [27] investigated the detailed airflow and heat rejection of individual cooling deltas. Yang et al [28] researched the aerodynamic field and temperature field of cooling deltas and found that the side deltas performed the worst under the influence of crosswinds.…”
Section: Introductionmentioning
confidence: 99%
“…However, as a critical heat transfer element, the heat transfer characteristics and aerodynamic fields of cooling deltas are also a research focus. Kong et al [27] investigated the detailed airflow and heat rejection of individual cooling deltas. Yang et al [28] researched the aerodynamic field and temperature field of cooling deltas and found that the side deltas performed the worst under the influence of crosswinds.…”
Section: Introductionmentioning
confidence: 99%